Pengaruh Pemberian Paket Edukasi SALINDI terhadap Pengetahuan Sikap dan Perilaku Sadari pada Remaja Putri di SMA N 10 Semarang - Kumala Bintang; Tutik Rahayu; Sri Wahyuni (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
Background: Breast cancer is one of the leading causes of death in women in Indonesia. Early detection through SADARI is important from adolescence, but many still lack the knowledge, attitudes, and behaviors necessary to implement it. Health education, such as the SALINDI education package, which contains interactive materials about SADARI. Aims: to determine the effect of providing the SALINDI education package on the knowledge, attitudes, and behavior of SADARI among adolescent girls at SMA Negeri 10 Semarang. Method: This research was conducted at SMAN 10 Semarang. The research design used was a Quasi-Experimental with Pretest-Posttest. The population was 100 female students in grade 11. The sampling technique used was purposive sampling with the Slovin formula, resulting in a sample size of 89 respondents. Normality tests were performed first, followed by bivariate tests using the Wilcoxon t-test. Result: The Wilcoxon statistical test for the effect of the Salindi Education Package on BSE knowledge, attitudes, and behavior showed a p-value of 0.000 <0.05. This indicates that the Salindi education package has an effect on BSE knowledge, attitudes, and behavior. Therefore, it can be concluded that the Salindi education package has an effect on improving BSE knowledge, attitudes, and behavior among adolescent girls at SMAN 10 Semarang. Conclusion: The Salindi education package has an effect on improving BSE knowledge, attitudes, and behavior among adolescent girls.